Chemical composition and relative basic density of two shrub white oak wood species from the Sierra de Álvarez, SLP, México - Bárcenas-Pazos, Guadalupe M.; Ríos-Villa, Rosalva; Aguirre-Rivera, J. Rogelio; Juárez-Flores, Bertha I.; Honorato-Salazar, J. Amador (Instituto de Ecología, A.C., 2016)
In the mountain range of Álvarez, San Luis Potosí eighteen oak species have been identified; two of them (Quercus sebifera and Q. tinkhami) included into the Quercus section or white oaks are shrubs. Currently, studies are not known on the wood characteristics of these species, which are only used locally in a reduced and rudimentary way.  Their chemical composition is presented here. Essays to estimate relative content (%) of lignin, extracts and ashes were carried out; specific gravity was also calculated along with volume of cellulose. Basic statistics were estimated for each parameter obtained. Variance analyses were applied between the essays sets of cellulose, lignin, ash, and extracts. Not significant differences (p > 95%) were found between species for cellulose and lignin. These results were similar to those presented by other authors for Mexican oaks. Ash volume resulted to be greater; it may be due to their particular climate and soil type, mainly. The extracts of Q. sebifera obtained by the ethanol-benzene mixture and by hot water were greater than those published for white oaks. These species were different (p > 95%) for extract content. Ash and extracts richness of these species seems to be related to their aridity adaptations. Relative basic density values for Q. sebifera were medium and high for Q. tinkhami.